Nursing Home Adaptation in Visually Impaired Older Adults Using a Narrative Approach,. (13th April 2021) - Toyoshima, Aya
Abstract: This study used a narrative approach to examine the difficulties that older visually impaired people experience when adapting to life in a nursing home. The interview data were collected from one blind aged person ( n = 1), focusing on the adaptation process from moving into the nursing home to the present and maintaining context of narrative that included the life history. Subcategories were extracted based on a framework of temporal coherence, causal coherence, thematic coherence, and situational coherence. This study revealed three factors related to adaptation to life in a nursing home for a visually impaired person, including psychological adaptation: becoming accustomed to life in the facility after changes in the living environment, having gratitude and maintaining "moderating human relationships, " and participating in activities connected to one's purpose in life. He was able to psychologically adapt and came to accept his death through an awareness of aging.